Editorial - Heitmeyer, Wilhelm; Massey, Douglas S.; Messner, Steven F.; Sidanius, James; Wieviorka, Michel (International Journal of Conflict and Violence (IJCV), 2008)
This time our focus section has guest editors for the first time. Miles Hewstone (University of Oxford, UK) and Douglas S. Massey (Princeton University, USA) have put together contributions addressing the field of neighbourhood and violence.